2019
DOI: 10.1111/jace.16313
|View full text |Cite
|
Sign up to set email alerts
|

Damage evolution in a self‐healing air plasma sprayed thermal barrier coating containing self‐shielding MoSi2 particles

Abstract: A self-healing thermal barrier coating (TBC) system is manufactured by air plasma spraying (APS) and tested by thermal cycling. The ceramic topcoat in the self-healing APS TBC system consists of an yttria stabilised zirconia (YSZ) matrix and contains self-shielding aluminium containing MoSi 2 healing particles dispersed close to the topcoat/bond coat interface. After spraying the healing particles the material was annealed to promote the formation of an oxygen impermeable Al 2 O 3 shell at the MoSi 2 -TBC inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…The STEM samples were in the form of thin lamellae prepared by FIB milling through the cross-section of the coating. More details about the STEM sample preparation procedure could be found elsewhere [39][40][41].…”
Section: Characterisationsmentioning
confidence: 99%
“…The STEM samples were in the form of thin lamellae prepared by FIB milling through the cross-section of the coating. More details about the STEM sample preparation procedure could be found elsewhere [39][40][41].…”
Section: Characterisationsmentioning
confidence: 99%
“…The continuous growth of TGO and some spinel Figure 8 shows the cross-sectional microstructure around the delaminated area after CTF tests. During thermal cycling, different thermo-mechanical properties between the matrix and healing agent could develop stress, so only 10 vol% of healing agents was blended with YSZ to minimize the development of stress, which was founded in other previous studies [27,29]. extrinsic toughening mechanism [41].…”
Section: Thermal Durability Evaluationmentioning
confidence: 99%
“…Furthermore, the healing agents were encapsulated by a sol-gel method to prevent their loss during coating fabrication, showing enhancement of oxidation resistance [28]. Chen et al [29] developed self-shielding healing particles, which produced an oxygen impermeable Al 2 O 3 shell, and identified crack-healing behavior during thermal cycling tests. Ouyang et al [30] introduced a SiC-based healing layer on the surface of the top coat, and showed the filling of the surface cracks and improved oxidation and spallation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the TBC lifetime is measured by the number of thermal cycles that the TBC can sustain until spallation. In order to arrest the cracks and potentially improve the TBC lifetime, researchers have investigated the implementation of self-healing particles within the coatings [3][4][5][6]. One of the most widely studied methods of incorporating self-healing properties in a TBC is to include encapsulated healing agents within the top coat, which is the location where cracks typically appear in TBCs (see Fig.…”
Section: Introductionmentioning
confidence: 99%